Book review: Archaeology & world religion - Badlihisham Mohd. Nasir,; Abdul Ghafar Don,; Gan, Wei Nie; Ismah Shamirah Ismail,; Nur Amira Mohd Zailani,; Raja Puteri Nurul Affiqah Raja Ahmad, (Department of Da'wah and Leadership Studies, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
This book, Archaeology and world religion is a book compilation from 8 writers or authors. Anders Bergquist -- Bergquist, Rev. Canon Dr Anders, St Albans Cathedral, St Albans, Hertfordshire, DilipChakrabarti -- Chakrabarti, Dr Dilip, Lecturer, Department of Archaeology, Universityof Cambridge, Downing Street, Cambridge, Robin Coningham -- Coningham, Dr Robin, Senior Lecturer, Department of ArchaeologicalSciences, University of Bradford, Bradford, Rachel Hachlili -- Hachlili, Professor Rachel, Chair of the Department of Archaeology, University of Haifa, Israel, Timothy Insoll --Insoll, Dr Timothy, Lecturer in Archaeology, School of Art History andArchaeology, University of Manchester, Oxford Road, Manchester, Paul Lane -- Lane, Dr Paul, Director, British Institute in Eastern Africa, PO Box30710, Nairobi, Kenya, Rachel MacLean -- MacLean, Dr Rachel, Honorary Secretary, British Institute in EasternAfrica, 10 Carlton House Terrace, London and Mike Parker Pearson -- Parker Pearson, Dr Mike, Reader, Department of Archaeology and Prehistory, University of Sheffield, Northgate House, West Street, Sheffield. It is the definitive text for this growing area of archaeology. The whole book can be divided to two parts, which can then be define by the survey done on each of the religions in question—Buddhism, Christianity, Hinduism, Islam and Judaism, and the second one is to address the important themes of ethics, gender and death.